PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PENERIMA PINJAMAN DENGAN METODE FMADM-SAW PADA KOPERASI WANITA NUSA INDAH BEKASI - Anna Mukhayaroh (LPPM Universitas Bina Sarana Informatika, 2017)
Abstract - Nusa Indah Women Cooperative Bekasi is a cooperative that has lending service to their members. Currently many members of cooperatives are applying for loans. Surely the Nusa Indah Bekasi Women's Cooperative faces problems in deciding which members of the cooperative are eligible to receive the loan. The loan decision from Nusa Indah Bekasi Women's Cooperative is related to various criteria such as member's age, member's job, the remaining maximum loan and the reason for the loan application. The number of members applying for loans makes the Nusa Indah Bekasi Women's Cooperative need to use decision support system to know the priority of the loan recipient so that the loan can be right on target. The decision support system in the selection of borrowers using the Fuzzy Multiple Attribute Decision Making (FMADM) method uses Simple Additive Weighting (SAW). In the study in tested 30 data cooperative members. Weighting is done for each criteria and final ranking so that it is known that most members are eligible for a loan. In this study also made software applications using Netbeans IDE 7.1 to assist in determining the priority of lending to members of the Nusa Indah Women Cooperative Bekasi. Key Word: SPK, FMADM, SAW